A magnetically retrievable copper ionic liquid nanocatalyst for cyclooxidative synthesis of 2-phenylquinazolin-4(3H)-ones. Issue 3 (22nd December 2020) - Gupta, Radhika; Arora, Gunjan; Yadav, Priya; Dixit, Ranjana; Srivastava, Anju; Sharma, Rakesh Kumar
Abstract : The present work reports the design and fabrication of a copper-containing ionic liquid supported magnetic nanocatalyst for the formation of 2-phenylquinazolin-4(3 H )-ones using o -aminobenzamide and benzaldehydes as the reaction partners. Abstract : In the present work, we report the design and fabrication of a copper-containing ionic liquid supported magnetic nanocatalyst via a convenient and straightforward synthetic approach for the formation of 2-phenylquinazolin-4(3 H )-ones using o -aminobenzamide and benzaldehydes as the reaction partners. The successful formation and properties of the as-prepared catalyst have been thoroughly investigated using diverse physico-chemical techniques including FT-IR, XRD, FE-SEM, TEM, ICP, VSM, BET and TGA. Using this nanocatalytic system, a variety of 2-phenylquinazolin-4(3 H )-ones are synthesized in excellent yields with operational ease and short reaction times in an environmentally preferable solvent under open air and without using any external oxidizing agent. Besides, the catalyst possessed facile magnetic recoverability and remarkable reusability for six consecutive runs without any appreciable decrease in the catalytic efficiency.